In Silico Primer Design for geographical detection of Apis florea using Cytochrome c oxidase subunit 1 (COX1) gene - Shullia, Nurul Insani; Kuswati, Kuswati; Kurniawan, Aditya; Fiarani, Hajar Syifa (Life Science and Biotechnology, 2023)
The yellow dwarf honey bee, Apis florea are well distributed in South Asia to South East Asia. This species is expanded and introduce area from their original distribution. However, the distribution of this honey bee in Indonesia is unexplored. The cytochrome c oxidase subunit 1 (COX1) gene are success to detect original geographic of introduce A. florea found in Egypt. The A. florea specific primer of COX1 gene are needed to produce the molecular marker for geographical origin detection. Thus, this study aims to in silico design the COX1 gene primer of A. florea using Primer3 and Primer-BLAST. This study results the best candidate primer of Af6_COX1_F and Af6_COX1_R primers that start from 212 to 983 regarding the A. florea COX1 gene (NC_021401) and produce 772 bp of amplicon. The melting temperature of forward primer are 54. 63 and 55.58Â°C, GC content of 40 and 45%, GC clamp of 3 and 2 for forward and reverse primer, respectively. There are no secondary structure of those primer and 100% homolog with A. florea COX1 sequences, thus those primer is potentially as the geographical origin marker of A. florea.